Neighborhood Safety and Major Depressive Disorder in a National Sample of Black Youth; Gender by Ethnic Differences - Shervin Assari; Cleopatra Howard Caldwell (MDPI AG, 2017)
Adolescence is a developmental period marked by increased stress, especially among Black youth. In addition to stress related to their developmental transition, social factors such as a perceived unsafe neighborhood impose additional risks. We examined gender and ethnic differences in the association between perceived neighborhood safety and major depressive disorder (MDD) among a national sample of Black youth. We used data from the National Survey of American Life - Adolescents (NSAL-A), 2003-2004. In total, 1170 Black adolescents entered the study. This number was composed of 810 African American and 360 Caribbean Black youth (age 13 to 17). Demographic factors, perceived neighborhood safety, and MDD (Composite International Diagnostic Interview, CIDI) were measured. Logistic regressions were used to test the association between neighborhood safety and MDD in the pooled sample, as well as based on ethnicity by gender groups. In the pooled sample of Black youth, those who perceived their neighborhoods to be unsafe were at higher risk of MDD (Odds Ratio [OR] = 1.25; 95% Confidence Interval [CI] = 1.02-1.51). The perception that one's neighborhood is unsafe was associated with a higher risk of MDD among African American males (OR=1.41; 95% CI = 1.03-1.93) but not African American females or Caribbean Black males and females. In conclusion, perceived neighborhood safety is not a universal psychological determinant of MDD across ethnic by gender groups of Black youth; however, policies and programs that enhance the sense of neighborhood safety may prevent MDD in male African American youth.